Put This On, Please : New & Selected Poems - Trowbridge, William, 1941- (Book collections on Project MUSE., 2014)
Contains work from all five of his full collections, as well as a group of new poems. In lines that capture the rhythms of everyday speech (with the ghost of meter haunting closely along), Trowbridge follows misfits and outcasts whose ramblings and shamblings reflect our own well-meaning gropes for fulfillment. These reader-friendly poems draw often from classic films and other elements of popular culture-- from Buster Keaton to Chuck Berry, from King Kong to Wile E. Coyote. Trowbridge is not squeamish about exploring the darker side of humanity, as in poems about the Kiss of Death, delivered by Michael Corleone in The Godfather II, or Nebraskan mass murderer Charles Starkweather. Capping off the book, a group of new poems takes a fresh look at old themes, sounding deepened notes of both melancholy and celebration. Throughout this seriocomic account of human foibles, vices, and wonders, Trowbridge makes a strong case for laughter as the only appropriate response to our post-post-modern condition.